PENGEMBANGAN MODEL PEMBELAJARAN PARENTING UNTUK MENINGKATKAN KECAKAPAN SOSIAL EMOSIONAL ANAK USIA DINI DI TK NEGERI PEMBINA KURIPAN - Mailandari, Mailandari (UNISAN JURNAL, 2024)
This type of development research uses a qualitative descriptive paradigm, field data is collected through interviews, questionnaires, observation and documentation. After conducting research and discussion, it can be stated that: (1) The concept of a parenting learning development model in the form of stimuli provided by educators to children has a significant role in optimizing children’s development, especially children’s social emotional development. The parenting patterns and behavior displayed by PAUD educators that are in line with the parenting patterns of parents will greatly determine the child’s overall educational success. (2) Developing a parenting learning model to improve children’s social emotions in PAUD can be carried out and started in the family environment by referring to foster parents’ patterns, attitudes and situations and conditions that surround parents which can influence children’s growth and development. (3) The development of parenting learning carried out at the Pembina Kuripan State Kindergarten can be improved by providing various information related to educational stimuli for children in the home environment. Apart from that, you can also familiarize yourself with routine activities that have been carried out related to learning children’s social emotional skills, for example helping or collaborating in tidying up/rearranging toys, waiting their turn, and sharing toys. Keywords: Children, Parenting Learning, Social Emotional.